L'História de Portugal du Círculo de Leitores, autour du genre de l’histoire nationale et des nations en Péninsule ibérique - Stéphane Boissellier (E-Spania)
In 1993 was published the monumental História de Portugal directed by José Mattoso. This work marked the Portuguese historiography, to the point of justifying its reissue twenty years later, and met an unprecedented public success. This achievement of Portuguese historiography is an opportunity to question what are these great « national histories », ranging « from the origins to the present day ». In the case of Portugal, which has fortunately lost its Salazarist focus on the nation’s “glory”, this kind of national history makes possible to formulate questions about the nature of the Iberian Peninsula, on the relationship between the Mediterranean and the Atlantic and on contacts between cultural formations. In doing so, we hope to pay tribute to Joseph Pérez, author of a Histoire de l’Espagne.